2022
DOI: 10.2169/internalmedicine.8507-21
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced Focal Pancreatitis Diagnosed by Endoscopic Ultrasound-guided Fine-needle Aspiration

Abstract: A 69-year-old man with advanced non-small-cell lung cancer was treated with pembrolizumab for 4 months. Three months after pembrolizumab was discontinued, computed tomography showed enlargement of the pancreatic head, with hypoattenuating areas in the pancreatic head to body. On endoscopic ultrasonography, the entire pancreatic parenchyma was hypoechoic. Endoscopic retrograde cholangiopancreatography showed narrowing of the main pancreatic duct at the pancreatic head. Endoscopic ultrasound-guided fineneedle as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Previous reports showed that the lymphocytes were predominantly CD8-positive lymphocytes; however, no such predominance was observed in the present case. irAEs are caused by an immune response triggered by T-cell lympho- (32,33). However, in the present patient, CD4 cells may have played an important role in the pathogenesis, as there were multinucleated giant cells and reaction-forming granulomas with dense fibrosis, which may explain why a predominant infiltration of CD8+ T cells was not observed.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Previous reports showed that the lymphocytes were predominantly CD8-positive lymphocytes; however, no such predominance was observed in the present case. irAEs are caused by an immune response triggered by T-cell lympho- (32,33). However, in the present patient, CD4 cells may have played an important role in the pathogenesis, as there were multinucleated giant cells and reaction-forming granulomas with dense fibrosis, which may explain why a predominant infiltration of CD8+ T cells was not observed.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, ICI-induced pancreatitis may not require strong activation of helper T cells or immunoglobulin production. Ikemoto et al and Hirota et al reported that irAE-induced pancreatitis showed significant infiltration with CD8 lymphocytes ( 32 , 33 ). However, in the present patient, CD4 cells may have played an important role in the pathogenesis, as there were multinucleated giant cells and reaction-forming granulomas with dense fibrosis, which may explain why a predominant infiltration of CD8+ T cells was not observed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation